2001
DOI: 10.1002/1098-108x(200103)29:2<205::aid-eat1010>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural research on anorexia nervosa: Assumptions regarding the role of body weight

Abstract: Objective To critically examine two assumptions guiding cross‐cultural research on the weight concerns of anorexia nervosa: (1) that weight concerns are specific to contemporary, Western manifestations of the disorder and (2) that the dissemination of Western values regarding thinness is primarily responsible for the development of anorexia nervosa in non‐Western contexts. Method A review of theoretical and empirical literature on cross‐cultural aspects of anorexia nervosa and the medical records of 14 Asian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 31 publications
0
61
1
Order By: Relevance
“…N. Robinson et al, 1996) and those living through rapid sociocultural transition (Abou-Saleh et al, 1996;Al-Adawi et al, 2002;Al-Subaie, 2000;Gordon, 2001). The fact that Western acculturation and explicit in-group evaluations were not associated with eating disorders symptoms both echoes (Haudek et al, 1999;Hill & Bhatti, 1995;Mumford et al, 1991), and contradicts previous findings in the field (Al-Subaie, 2000; Eapen et al, 2006) further adding to the equivocation surrounding the relationship between explicit measures of Western acculturation and eating disorders symptomatology (Rieger et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N. Robinson et al, 1996) and those living through rapid sociocultural transition (Abou-Saleh et al, 1996;Al-Adawi et al, 2002;Al-Subaie, 2000;Gordon, 2001). The fact that Western acculturation and explicit in-group evaluations were not associated with eating disorders symptoms both echoes (Haudek et al, 1999;Hill & Bhatti, 1995;Mumford et al, 1991), and contradicts previous findings in the field (Al-Subaie, 2000; Eapen et al, 2006) further adding to the equivocation surrounding the relationship between explicit measures of Western acculturation and eating disorders symptomatology (Rieger et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…This assumption however requires a critical re-examination, especially in light of conflicting findings (Rieger, Touyz, Swain, & Beumont, 2001). Not only have several studies failed to find the anticipated positive relationship between Western acculturation and eating disorders symptoms (Haudek, Rorty, & Henker, 1999;Hill & Bhatti, 1995), at least one study has even reported the opposite link.…”
Section: Implicit Out-group Preference and Eating Disorders Symptomsmentioning
confidence: 99%
“…5,16,20,[23][24][25][26]38 Notably, the majority are authored or co-authored by Professor Sing Lee, a psychiatrist and medical anthropologist credited with characterizing this phenomenologic variant. However, NFP-AN has also been reported in other nonWestern populations, including in Singapore, 14,21 West Malaysia, 19 Ghana, 27 and India 39 as well as in Asian patients residing in Australia 4 and in South Asian patients residing in the United Kingdom. 22,36 Moreover, two studies reporting the relative frequency of NFP-AN in South Asian versus 'White' AN patients in the United Kingdom found that NFP-AN was relatively more common in South Asians 36 ; however, one of these studies reported that ''sensitivity to 'fatness''' was ''invariably revealed'' during treatment.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…In multi-ethnic communities it is often helpful to distinguish between cultural norms and potential diagnostic features, particularly because cultural factors influence body weight norms, weight control, obesity, and body image (BI), body image dissatisfaction, and consequently may both obscure or increase vulnerability for ED [618]. At the same time in anorexia nervosa (AN), BI dissatisfaction is an essential diagnostic and together with the drive for thinness is extreme and underlies and perpetuates the psychopathology [8, 15, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Women, especially adolescent, are more likely to experience BI concerns [2, 7, 9, 18, 21, 22]. Social norms of feminine beauty, particularly western norms of shape and body weight are consistently correlated with increased weight consciousness and risk of ED [1416, 21, 23, 24].…”
Section: Introductionmentioning
confidence: 99%